Influence : The Psychology of Persuasion - Cialdini, Robert B. (New York : Harper Business, 2021)
"In this highly acclaimed New York Times bestseller, Dr. Robert B. Cialdini-the seminal expert in the field of influence and persuasion-explains the psychology of why people say yes and how to apply these principles ethically in business and everyday situations"--
Includes bibliographical references and index.
Keywords: Influence (Psychology); Persuasion (Psychology); Compliance